Social Rehabilitation for Persons with Disabilities A Case Study on Social Rehabilitation Institution for Persons with Disabilities in Cibabat, Cimahi, West Java. - Habibullah Habibullah; Agus Marzuki (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2014)
Social rehabilitation services for persons with disabilities organized by institution has advantages and disadvantages. One of the disadvantages is its limited capacity if compared with disabilities population who need social service. The results of this study reveals that the social rehabilitation services input in the form of clients, human resources, facilitiy and infrastructure, culture, theory/methods and relative feedback has been relatively fulfilled. Operational conversion, supported by structural component and functional processes has been implemented but not optimal. Social rehabilitation services output have made some clients working independently, either by opening their own business or working in the company.